Recent Experiments in Social Accounting: Flexible and Dynamic Budgets - Tinbergen, J.; Derksen, J. B. D. (Econometrica, 1949)
In recent years increasing use has been made of systems of social accounts, and a variety of new types and new forms of presentation have been suggested. The general features of such systems are: (a) the division of an economy into a number of groups or economic entities, mostly themselves a complex of elementary units, and (b) a summing up in the form of accounts of the transactions of various kinds between these economic entities. As a rule, the economy of one country is investigated, implying that all other countries are regarded as one single group. The economy considered may be split up into a number of separate groups. It is customary to distinguish between consumers' households, business enterprises, and the government sector. If special attention is to be given to banking problems for example, banks will constitute a separate group.